RANCANG BANGUN SISTEM SOLAR CHARGING STATION BERBASIS ARDUINO MEGA2560 DILENGKAPI PEMBATASAN DAYA BEBAN - ., Zaenurrohman; Hazrina, Fadhillah; Mafaza Harris, Ridho Ihsan; Santoso, Agus; Bahasa Indonesia (Politeknik Negeri Cilacap, 2024)
The widespread use of smartphones in public places has driven the adoption of power banks as a solution for power needs. However, power banks have several drawbacks. To address these needs in public places, charger station systems have been widely implemented, including solar panel-based charger stations as their power source. These developments have also extended to commercial applications, allowing the use of charger station facilities in public places to be subject to specific charges. In this study, a solar charger station system with coin-operated payment for electricity was developed. Additionally, for system security, a feature was added to limit the current flow to the load to a specific amount. The charger station was built using several components, including solar panels, solar charge controllers, and batteries, which are integrated to produce electricity. An inverter is used to convert DC current into AC current, which is then connected to electrical terminals via a solid-state relay switch. Arduino Uno is used to control the electrical connection from the inverter to the terminal through the solid-state relay based on data from the coin acceptor and the PZEM-004T sensor. An LCD is also used to display information required by the users. The test results showed that the solar charger station system could successfully charge smartphones using 1,000-rupiah coins with a 100% success rate. With a rate of 1,000 rupiahs per 40Wh, the charger station system can disconnect the power supply to each load after consuming 40Wh of electricity. Additionally, the system is capable of disconnecting the load when the attached load exceeds 40W.